2018
DOI: 10.1016/j.joco.2017.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Fungal keratitis caused by rare organisms

Abstract: PurposeTo report two rare cases of filamentous fungal keratitis.MethodsTwo non-consecutive patients presented with suspicious fungal keratitis. After performing the smear and culture, medical therapy was started for them. They underwent slit photography and in vivo confocal microscopy (IVCM) in their follow-up visits.ResultsThe patients were 33-year-old and 56-year-old farmer men. They both mentioned a history of ocular trauma by plants. During their follow-up visits, corneal infiltration density and fungal hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…Five of our seven patients had trauma history, which agrees with findings in previous reports that ocular trauma was the primary risk factor for Colletotrichum keratitis . Because the conidia of Colletotrichum are not freely released, the traumatic implantation is essential for initiation of the infection .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Five of our seven patients had trauma history, which agrees with findings in previous reports that ocular trauma was the primary risk factor for Colletotrichum keratitis . Because the conidia of Colletotrichum are not freely released, the traumatic implantation is essential for initiation of the infection .…”
Section: Discussionsupporting
confidence: 90%
“…Their ITS and ACT sequences are nearly identification to those of the type species of Five of our seven patients had trauma history, which agrees with findings in previous reports that ocular trauma was the primary risk factor for Colletotrichum keratitis. 2,[9][10][11][12][13][14]16,[19][20][21]23,25 Because the conidia of Colletotrichum are not freely released, the traumatic implantation is essential for initiation of the infection. 8,11,39 The other one patient had regular antineoplastic treat- However, all reported patients with C. truncatum, including previously documented six (Table S1) and our two cases, required surgical interventions, such as therapeutic keratoplasty and evisceration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 100 species have been reported as pathogens of fungal keratitis, Fusarium species are the most commonly isolated pathogens, followed by Alternaria and Aspergillus species, in Shandong Province, China [10][11]. In the recent years, the incidence of uncommon fungal keratitis caused by rare species with diverse morphology has greatly increased [12][13][14][15][16][17][18][19]. The current study described the first confirmed series of fungal keratitis cause by V. dahliae with detailed descriptions of clinical characteristics and treatment outcomes.…”
Section: Discussionmentioning
confidence: 95%
“…2010; Tabatabaei et al . 2018). In developing countries like India, the traditional therapies used by rural people for ocular infections include the application of extracts of green leaves, banyan tree juice, goat and human breast milk, castor and coconut oil, and chicken blood (Thomas 2003).…”
Section: Pathogenicity Of Dhmentioning
confidence: 99%